Jeszcze o przyszłości prawa rolnego - Budzinowski, Roman (Wydawnictwo Naukowe UAM, 2010)
The question concerning the future of agricultural law is not only academic in nature. It pertains to essential issues on the functioning of economy, particularly agricultural economy, thus is has a political, social or economic aspect, being not only local, but also global. It is an issue important not only for agricultural producers themselves, but also for consumers, i.e. for the broadly understood general public. For specialists in agricultural law its special importance is not limited to the Hamlet’s hesitation over to be or not to be. The paper constitutes a supplementation and deepening of considerations contained in the paper on “The future of agricultural law”, published in Przegląd Prawa Rolnego 2009, no. 1. The Author presents mechanisms of development for regulations concerning agricul-ture and fields related to agriculture, modifications of the object of this regulation and methods of its influence and – in view of the above – the development of science on agri-cultural law.